Being-Towards-Death-and-Resurrection: An Examination of Finitude and Infinitude in the Writings of Martin Heidegger and Emmanuel Falque - Siemens, Braden (My University, 2020)
This thesis gives an account of Heidegger’s understanding of anxiety and death as it relates to the Christian theology of resurrection. It does so by investigating three primary accusations that Heidegger makes against Christianity with respect to its views on death and anxiety interpreted through a belief in an afterlife. In order to interact with Heidegger’s criticisms, Christian phenomenologist Emmanuel Falque’s work is explored for a more dialogical Heideggerian and Christian understanding of death. In doing so, this thesis picks up questions such as: can resurrection interpreted phenomenologically contribute something new to a Heideggerian view of Dasein as a Being-towards-death? as well as in what ways can Heidegger’s starting-point of finitude formulate new possibilities for interpreting Christ’s death and resurrection? Are these theological events necessary for an “authentic” understanding of death and finitude? These questions pertain to anxiety about what Heidegger calls the “to-come”, a concept mapped out in Heidegger’s own work on Christianity and then secularized in his fundamental ontology delineated in chapter one. Chapter two takes up Falque’s work on the death of Jesus and its correlations to Heideggerian views on death, while chapter three contemplates resurrection (and through this, birth) and the various modes of being that it opens up for human finitude. Chapter three concludes with a Levinasian reading of the New Testament resurrection accounts in order to consider how the Christian mode of Being-towards-resurrection can work alongside and, in a certain sense, within a Heideggerian view of human finitude as a Being-towards-death.
Keywords: Heidegger Death Resurrection Falque Levinas